Longitudinal growth study of male Japanese junior high school athletes - Nariyama, K.; Hauspie, R. C.; Mino, T. (American Journal of Human Biology, 2001)
The aim of this study was to establish the pattern of adolescent growth in height of male Japanese athletes, and to compare their growth with appropriate controls. The sample consisted of 126 baseball, 39 basketball, 83 soccer, and 53 volleyball players, and 36 nonathletes. The data were collected retrospectively in six public schools in Fukui Prefecture of Western Japan between 1970 and 1987. All subjects were measured at yearly intervals between the age of 6 and 18 years. The total number of measurement occasions for the 337 subjects amounted to 4,134. Athletes trained between 13 and 18 h/week. Individual growth patterns were determined by fitting Preece Baines model I to each individual's serial data. Various biological parameters were derived from the fitted curves. The results indicated that the average growth pattern of these adolescent athletes did not differ substantially from the control group. Volleyball players were significantly taller at 18 years (+3 cm) than the nonathletes (Student's t-test, P < 0.05). Soccer players showed a slight tendency towards late maturation with age at take-off and at peak velocity about half a year later than in nonathletes (Student's t-test, P < 0.05). The 2.3 cm gain in body height due to the later onset of the pubertal growth spurt in soccer players was counterbalanced by a 0.7 cm smaller prepubertal height and a 0.9 cm smaller adolescent gain, so that they ended up slightly, but not significantly, taller than the controls (+0.7 cm). The small differences in growth pattern observed between the nonathletes and the various sports suggest that, in contrast with top-level athletes, body size and maturation rate were not important selective factors in the various groups of athletes of the present study.